Communication Model of Three Indonesian Presidential Candidates Ahead of the 2024-2029 Election on Social Media Twitter - Putri, Aulia Kartika; Habibullah, Akhmad; Zainudin, Arif (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
Government communication is an instrument used to disseminate information to the public. Political communication is any form of communication that involves political messages, political players, or anything related to authority, executive branch, or public policy. The percentage of Twitter users in Indonesia is increasing rapidly from year to year, along with the increase in social media users. Even 6.43 million users, or around 52% of all social media users in Indonesia, were Twitter users in 2019. The holding of elections is an important moment in the democratic process in Indonesia. This research looks at existing communication patterns between exhibitionists and the public in conveying information about the communication patterns of the three 2024-2029 presidential candidates through Twitter media. This research uses qualitative methods with a descriptive approach to data analysis using NVivo Plus 12 software, starting with data input through the NCapture Nvivo feature on the official accounts of the three presidential candidates @aniesbaswedan, @ganjarpranowo, and @prabowo, then coding, exploration, data visualization and, data presentation and conclusions. The result is that Ganjar Pranowo is the most active presidential candidate on Twitter social media compared to Anies Baswedan and Prabowo Subianto, with a percentage of 9.15% in the April-June 2023 quarter.